Neurodegeneration: A Tale of Microbes and Neurons - Octavian Costin IOGHEN; Mihaela Roxana IOGHEN; Bogdan Ovidiu POPESCU (Modern Medicine)
The gut-brain axis has emerged as a central paradigm in understanding the bidirectional relationship between the gastrointestinal microbiota and the central nervous system (CNS), particularly within the context of neurodegenerative disorders. This review synthesizes contemporary insights into how microbial dysbiosis and vagal pathways orchestrate critical processes in neurodevelopment and neurodegeneration. We dissect the multifaceted mechanisms by which microbial constituents, including lipopolysaccharides, bacterial amyloids, and amphiphilic compounds, penetrate host barriers such as the blood-brain barrier, contributing to neuroinflammation, protein misfolding, and neuronal dysfunction—hallmarks of diseases like Parkinson’s disease, Alzheimer’s disease, and multiple sclerosis. Although preclinical models present compelling findings, the need for longitudinal, large-scale clinical investigations remains critical. This synthesis underscores the gut microbiota as a therapeutic target within a precision medicine framework aimed at mitigating neurodegenerative disease onset and progression.